"One planet" cities sustaining humanity within planetary limits - Thorpe, Dave 1954- (Routledge, 2019)
This book addresses the crucial question of how the essential needs of the growing human population can be met without breaking the Earth's already-stretched life-support system. With four out of five people predicted to be urban dwellers by 2080, 'One Planet' Cities proposes a pathway to genuine sustainability for cities and neighbourhoods, using an approach based on contraction and convergence. Utilising interviews with key players, including the Global Footprint Network, World Future Council, WWF, mayors and government officials, and case studies from across the globe, including Europe, North and South America, Australia, South Africa, China and India, David Thorpe examines all aspects of modern society from food provision to neighbourhood design, via industry, the circular economy, energy and transport through the critical lens of the ecological footprint and relevant supporting international standards and indicators. Recommendations on managing supply chains and impacts, how the transition to a world within limits might be financed, and a deep examination of the Welsh Government's pioneering efforts follow. It concludes with an imagined vision of what a genuinely sustainable future might be like, and an appeal for 'one planeteers' everywhere to step up to the challenge. This book will be of great interest to practitioners and policymakers involved in governance, administration, urban environments and sustainability, alongside students of the built environment, urban planning, environmental policy and energy